Fabrication of La3+ doped Ba1−xLaxTiO3 ceramics with improved dielectric and ferroelectric properties using a composite-hydroxide-mediated method. Issue 8 (10th February 2023) - Younas, U.; Atif, M.; Anjum, A.; Nadeem, M.; Ali, T.; Shaheen, R.; Khalid, W.; Ali, Z.
Abstract : The improved dielectric and energy storage properties of La 3+ -doped BaTiO3 ceramics make them attractive for use in energy storage applications. Abstract : Lanthanum (La 3+ ) doped Ba1− x La x TiO3 ( x = 0.0, 0.0025, 0.005, 0.0075) ceramics were synthesized by the composite-hydroxide-mediated method. Rietveld refinement of the XRD patterns confirmed the formation of a perovskite crystal structure that transforms from tetragonal to pseudo-cubic with La 3+ doping content ( x ). Scanning electron microscopy displayed a dense and homogeneous microstructure with reduced grain size on La 3+ doping. The frequency and temperature-dependent dielectric measurements showed an improvement in the dielectric permittivity, a decrease in the ferroelectric–paraelectric transition temperature, and an increase in the dielectric diffusivity with increasing La 3+ doping content. Complex impedance analysis indicated the semiconducting behavior with a positive temperature coefficient of resistance effect, which could be explained in terms of a charge compensation mechanism in the donor doped BaTiO3 . The ferroelectric hysteresis loops revealed that these ceramics are ferroelectric in nature, while an improvement in the energy storage density and energy storage efficiency was observed for the doped samples due to reduced grain size on La 3+ doping. Here, the sample with x = 0.005 has a high dielectric permittivity, a low dielectric tangent loss, and the highest energy storage efficiency. This makes this composition interesting for energy storage applications.